Curriculum development in the postmodern era : teaching and learning in an age of accountability - Slattery, Patrick, 1953- (New York : Routledge, 2013)
"The 3rd edition of this introduction to and analysis of contemporary concepts of curriculum that emerged from the Reconceptualization of curriculum studies brings readers up to date on the major research themes within the historical development of the field"--
pt. I. Curriculum development as a field of study -- pt. II. Complicated conversations in contemporary curriculum development -- pt. III. Curriculum development in the postmodern era.
Includes bibliographical references and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Curriculum planning; Curriculum change; Education -- Curricula -- Philosophy; Postmodernism; Electronic books